Application of different nitrogen doses in fertirrigated cacao seedlings (Research, Society and Development, 2021)
The Medicilândia municipality is the main dried cocoa beans producer in Pará state, however, researches are being carried out in relation to the seedlings production. The study objective was to study the cacao seminal seedlings growth under a drip irrigation system, receiving different nitrogen doses with fixed doses of phosphorus (4,5 g) and potassium (3 g) through fertirrigation. The experiment was realized under greenhouse conditions with four treatments and five repetitions in a design of randomized blocks, being each composed by seven plants. Thus, T1 = check, without fertilization; T2 = 2 g of N + P and K; T3 = 7 g of N + P and K; T4 = 12 g of N + P and K. The treatments were scientific from the 31st to the 156th day after sowing, where the values of height, collar diameter and leaves number were obtained fortnightly. On the 156th day, the plants were harvested and obtained the root length, fresh matter and aerial part dry matter and root and the nutritional contents from the leaf and root plant tissue. The plants obtain results with the highest values of height, collar diameter and leaves number in the T2 treatment.